Da passagem à atenuação: Jenner e Pasteur e o desenvolvimento dos vírus inoculáveis - Silva, Camila Sloboda Pacheco da (2015)
Vaccination is a relevant scientific development that became a means for disease prevention and conservation of the state of health of large populations. In 1798, Edward Jenner developed the smallpox vaccine by subjecting to experimental testing the hypothesis that inoculation of cowpox matter passed to and among humans protected against smallpox. Later on, in 1888, Louis Pasteur applied the method of passages between different animal species to attenuate infectious matter of various diseases and tested the effectiveness of the resulting vaccines. The aim of the present study was to identify continuities and discontinuities in the development of vaccines for nearly one hundred years within various contexts like the mythical-religious, the empirical and the medicalscientific. The study of the scientific work performed in Pasteur s laboratory allowed us map the development of the concepts of vaccine and vaccination, as well as to outline changes in the methods to elaborate vaccines for avian cholera, anthrax and rabies. In addition, we were able to locate common elements in Jenner and Pasteur s ideas and methods, to wit, passage of infectious matter between species, attenuation of virulence via interspecific inoculation, non recurrence of disease in vaccinated individuals, and verification of the immunizing action of vaccines